ON THE GROWING SOCIAL ROLE OF UNIVERSITIES UNDER KNOWLEDGE SOCIETY - Orzhel, Olena; Tryma, Kateryna (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2020)
The paper intends to investigate the social role of higher education institutions (HEIs) under knowledge society. As knowledge becomes the main asset and driver of social-economic transformations in the 21st century, HEIs are positioned as centres where knowledge is generated, accumulated, disseminated and applied. With emergence of knowledge society, university mission “to contribute to the public good” is becoming more visible and tangible in HEIs’ operations. Responding to community needs or societal demand, HEIs will liaise and/or compete domestically and internationally with other state and non-state actors: non-governmental organizations (NGOs), authorities, interest groups, local communities. Both competition and cooperation may produce win-win effect, or end up with win-lose or lose-lose result.Case study method will be used to research different cooperation patterns between HEIs and other actors. In more detail, relationship between HEIs and NGOs will be explored to test the hypothesis that NGOs, who have been leaders in societal change over the last three - four decades, are losing primacy to HEIs. We will examine the social role of HEIs and their cooperation with civil society in situation of emergency, when societal demand for knowledge, expertise and response to crisis is high. In detail, we intend to look at Mariupol State University – a HEI with strong community ties and reputation of a civic university – in order to examine its community service and interaction with municipal knowledge hubs during hybrid war unleashed in 2014. Therefore, the aim of this research paper is to investigate whether and how under knowledge society the social role of HEIs changes in emergency situations and outline their possible contribution to problem-solving in cooperation with other partners, first of all NGOs. Key words: higher education institutions, non-state actors, non-governmental organizations, knowledge hub, knowledge economy.